AWARENESS, PERCEPTION AND ACCEPTABILITY OF MENSTRUAL CUPS AS AN ALTERNATIVE MENSTRUAL HYGIENE MANAGEMENT AMONG COLLEGE TEACHERS OF PERAMBALUR DISTRICT, TAMIL NADU. (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Millions of women globally experience menstruation every month. It is normal biological process. The start of menstruation indicates the start of the reproductive years in female life. The menstrual cup is a recently developed alternative to sanitary napkins. These cups are made from higher level medical grade silicone, latex, rubber, or elastomer and when inserted inside the vaginal canal and are capable of collecting menstrual flow.Objective: To assess the level of awareness, perception and acceptability of menstrual cups and also    their hygiene among Women in the reproductive age.Material and methods: A cross sectional study was conducted at a private college, with a study population about 245. The study Participants were women aged 18-45years. Women who attained menopause were excluded in the study.Results: The majority of study participants belonged to 31 to 40 years of age (43.5%).Among participants 89.4% was using sanitary pads. Only about 37.3% of the study population knew about menstrual cups. Most (42.7%) of them gathered information about menstrual cups from mass media/Internet. 35.7% of them knew that menstrual cups were safe. About 22.1% of them correctly knew that menstrual cups can be emptied in 6 to 12 hours. A large proportion 64.2% knew that boiling was the proper method of sterilization of menstrual cups.Conclusion: The stigma around menstruation is still prevalent in India. Majority of them are sticking with sanitary pads, still many lacks on knowledge in solid waste disposal. Green menstruation, sustainable menstruation, looking after our planet, so promoting menstrual cup usage is the need of the hour. Awareness programs should be conducted by the Government and free menstrual cups should be distributed.